Seed oleosomes of Jatropha curcas L. as diversity estimators in populations of Southern Mexico - Adriano-Anaya, M. L.; Gómez-Pérez, J. A.; Ruiz-González, S.; Vázquez-Ovando, J. A.; Salvador-Figueroa, M.; Ovando-Medina, I. (Grasas y Aceites, 2014)
In this work, we used oleosome data to estimate the variability in eight J. curcas populations of Southern Mexico, using a multivariate approach. We found spherical oleosomes with diameters between 2.18 μm and 4.15 μm, which have two types of spatial arrangements: clustered and dispersed. A discriminant analysis showed that populations with more differentiation are Oaxaca and Veracruz, while Isthmus was the most diverse. The most informative variables for their contribution to the discriminant functions were oleosome size and number of oleosomes·μL of tissue−1. A heritability study with seeds harvested in two consecutive years showed that the variables oleosomes·μL of tissue−1 and oleosomes per cell have high broad sense heritabilities (h2bs=94.3% and h2bs=92.2%, respectively). A cluster analysis revealed high levels of dissimilarity between individuals. Correlation was found between the ratio oleosomes/tissue (volume/volume) and total oil content of the seed. The identification of genotypes with contrasting characteristics could provide the basis for future studies of the inheritance of characters in J. curcas.